Roofs and Walls of Buildings as a Media for Converting Solar Thermal Energy into Electrical Energy - Rifky; Agus Fikri; Mohammad Mujirudin (Procedia of Engineering and Life Science, 2021)
Solar energy can be used by buildings. Parts of the building can convert solar thermal energy into electrical energy.The roof and walls are the parts of the building that receive the most sunlight. Therefore, the roof and walls of the building can supply electricity with the thermoelectric generator. The aim of this research is to get the maximum possible output power from the thermoelectric generator system. From the output power produced, it will be possible to find the feasibility of a thermoelectric generator to be used as an energy source for the roof and walls of the building model. The building model is designed simply where the roof and walls can be located a thermoelectric generator system, which consists of a heat sink, a thermoelectric circuit and a cooling system. The heat sink used is aluminum. The thermoelectric circuit consists of 15 sets which are assembled in a series connection arrangement. The cooling system used is active cooling, where water as the cooling fluid circulates continuously during the operation of the system. The thermoelectric hot side temperature is obtained from solar thermal radiation through a heat sink. Meanwhile, the temperature on the cold side of the thermoelectric is the result of the effect of the cooling system that is attached. The temperature difference between the hot and cold sides of the thermoelectric produces a system output in the form of electric voltage and electric current. This study obtain that the generator system on the roof with a temperature difference of 8.90 oC on the hot-cold side produces a power of 1.953 watts. While the generator system on the wall with a temperature difference between the hot-cold side of 1.80 oC produces a power of 0.030 watts.